Experimental tests of LiSn alloys as potential liquid metal for the divertor target in a fusion reactor. (August 2017) - Tabarés, F.L.; Oyarzabal, E.; Martin-Rojo, A.B.; Tafalla, D.; de Castro, A.; Medina, F.; Ochando, M.A.; Zurro, B.; McCarthy, K.; ,
Highlights: Insertion of a LiSn sample into the edge of TJ-II does not lead any significant perturbation of plasma parameters. Zeff values below 1.5 and very low Prad/Pin values (<2%) were deduced even with hot samples at the LCFS. Conversely, plasma operation became impossible if the SS support (finger) is uncovered. Only Li emission was detected. No traces of Sn were detected by visible and UV spectroscopy. H recycling did not evolve with temperature. H retention values of ∼0.01% H/(Sn + Li) at T < 450 °C were deduced from TDS at the laboratory (gas exposure). Agreement with previous reports and in situ TDS in TJ-II. Poor thermal conductivity of the CPS of LiSn was deduced for a damaged SS mesh. Abstract: The first experiments of exposure of a LiSn alloy (Li/Sn atomic ratio = 20/80) to a hydrogen plasma in TJ-II are here presented. Solid and liquid samples have been inserted at the edge and evidence of sample melting of a solid sample during plasma exposure has been observed. A negligible perturbation of the plasma has been recorded, even when stellarator plasmas are particularly sensitive to high Z elements due to the tendency to central impurity accumulation. Melting of the sample by the plasma thermal load did not lead to any deleterious effect on the plasma performance. Strong lithium emission was detected at the LiSn sample but no sign of Sn contamination and low values of Zeff and radiated power were deduced. Hydrogen recycling was studied at two different temperatures and no change was detected in the range of 300–750 K. The retention of H2 by the alloy was addressed in separate experiments at the laboratory. Values in the order of 0.01% H/(Sn + Li) were deduced in agreement with in situ TDS analysis of the plasma exposed samples and previous reports.